Les contradictions des réformes de l'eau potable en Colombie. L'exemple de l'aire métropolitaine de Bogotá - Vincent Gouëset (Cybergeo)
The case of the metropolitan area of Bogota shows that the reforms of the water supply system in Colombia, inspired by principles of democratization, sustainable development and economical liberalization, cannot be applied, because of the contradictory aims of these principles.